ACCESS TO MEDICINES STRATEGIES OF THE NATIONAL CANCER CONTROL PROGRAMME IN CAMEROON - Edo’o, Vanina Doris; Atenguena, Etienne; Essomba, Marie Josiane Ntsama; Abenwie, Suh Nchang; Nga, Emmanuel Nnanga; Hervé, Jim Nemy; Essomba, Thérèse Mbezele; Ahidjo, Yaya; Ndom, Paul; Essi, Marie-José (Universal Journal of Pharmaceutical Research, 2021)
Objective: Access to cancer drugs is a public health concern in low and middle-income countries. In Cameroon, the National Cancer Control Programme (NCCP) faces various obstacles to ensure accessibility of cancer drugs. This research aims to analyse the strategies implemented by the NCCP to ensure drugs selection and supply chain management,and obstacles encountered at the central level. Methodology: A qualitative cross-sectional situational analysis was carried out at the NCCP and the National Essential Medicines Supply Central (NEMSC)in Yaounde. For this purpose, tape-recorded interviews were conducted with key informants using two interview guides. After transcription, the verbal data were kept in a textual corpus and rendered in verbatim. The content analysis was done manually on the basis of a dimension matrix. SPSS version 20 was used to determine descriptive parameters like frequencies and means. Results: 47% of the drugs retained were part of the National list of essential medicines. The NEMSC ordered 13 princeps. Among these, 35% had generics on the market. In logistics chain management, drug needs estimation and supply planning were based on approximation. As there was no sure information trackability and coordination between actors, not ensured. Also, a monitoring and evaluation plan had not been put in place. Furthermore, the only source of funding was the Government through the annual budget line. Limited financial resources allocated to supply was the main bottle neck, due to the high cost of the therapies and the ever-increasing demand. This resulted in a long stock-out(up to 15 months) for all the drugs and complete unavailability for others, like morphine, despite its great palliative care demand. Conclusion: There are many challenges around cancer drugs accessibility in Cameroon. Therefore it is an urgent need to strengthen drug provision services within the NCCP. Peer Review History: Received: 5 August 2021; Revised: 9 September; Accepted: 12 October; Available online: 15 November 2021 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewers: Dr. A.A. Mgbahurike, University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Dr. Muhammad Zahid Iqbal, AIMST University, Malaysia, drmmziqbal@gmail.com